Effect of Fear, Concern, and of Risk Factors for Complicated Covid-19 on Self-Care in People in Pre-elderly and Elderly Stages - Medina-Fernández, Josué Arturo; Medina-Fernández, Isaí Arturo; Torres-Soto, Nissa Yaing; Cortez-González, Luis Carlos; Rascón-Arriaga, Fernanda Guadalupe; Cortes-Montelongo, Diana Berenice (Investigación y Educación en Enfermería, 2023)
Objective. The work sought to determine the effect of the risk factors, fear, and concern on self-care regarding COVID- 19 in people in pre-elderly and elderly stages. Methods. Correlational-predictive study, gathered through convenience sampling. The study applied the scale of fear of COVID-19 (Huarcaya et al.), the scale of concern about COVID-19(Ruíz et al.,), and the scale of self-care during the COVID-19 confinement (Martínez et al.,). Descriptive and inferential statistics were applied as the mediation model based on regression. Results. The study had the participation of 333 people, with the majority being women (73.9%). Correlation was found between self-care with the scores from the scale of fear (r = -0.133, p <0.05) and of concern (r = -0.141, p<0.05) regarding COVID-19. The direct effect of the model wasc’ = 0.16, [95% BCa CI = -0.28, -0.09]. The standardized value for the indirect effect was estimated as c = -0.14, [95%BCa CI=-0.23,-0.09]), which shows existence of a 14.0% effect of the mediating variable on self-care conducts in the prediction model. Conclusion. A direct effect exists of risk factors for COVID-19 complication on self-care, mediated by concern and fear, besides explaining by 14% the self-care conducts for COVID-19. Recommendation is made to address other emotional variables to consider if these increase the prediction.